(untitled) (LEARNing Landscapes, 2016)
All my adult life I have been a language and literacy educator in school and university classrooms. And for most of my adult life I have also been a poet. I read and write poetry; I teach poetry; I write about teaching poetry and about why poetry is important for living creatively in the world. In my poems I seek to remain open to possibilities for living poetically. I seek to see with the eyes of the heart and to hear with the ears of the heart. In a sequence of poems, citations, and ruminations, I ponder the signi cance of poetry.